Mapping research trends based on Tenopir taxonomy in Berkala Ilmu Perpustakaan dan Informasi Journal - Siti Rohaya; Darofi Duwi Lestari (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This study aims to map research trends based on the Tenopir taxonomy from one of the reputable journals in information and library science in Indonesia: the journal of Berkala Ilmu Perpustakaan dan Informasi (BIP). Research Methods. This quantitative descriptive research used a co-word analysis approach and subjects are grouped using Tenopir taxonomy. Data Analysis. The data collected are 108 BIP journal articles from 2019-2023. Theywere analyzed using a reference management tool Zotero and microsoft excel then all data were processed using VOSviewer using Tenopir taxonomy. Results. Mapping research trends in 2019 - 2023 based on keywords found 5 highest keywords subjects: [1] COVID-19, [2] library, [3] librarian, [4] archives and [5] bibliometrics. Meanwhile, based on the standardization results, we found [1] library science, [2] librarianship, [3] management, [4] social legal & ethical aspects of information and [5] archives. However, the study of information technology showed the peak in 2023. This shows that information technology is an important part of libraries and information dissemination, and can be predicted to be the next topic trend. Conclusions. Mapping articles using the Tenopir taxonomy is effective to expand the theme of study as one theme can be executed to be several studies. This can be the focus and scope of articles to show the research trends in BIP journals.